2009
DOI: 10.4314/eamj.v85i3.9634
|View full text |Cite
|
Sign up to set email alerts
|

Causes And Pattern Of Unilateral Hand Injuries

Abstract: Objective: To assess the causes and pattern of hand injuries in patients with isolated unilateral acute hand injuries managed at the Kenyatta National Hospital (KNH). Design: A prospective cross-sectional descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In developed countries falls are a leading cause of hand injuries [11]. In a recent Kenyan study, falls were the third most common cause of hand injuries after occupational injury and assault [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developed countries falls are a leading cause of hand injuries [11]. In a recent Kenyan study, falls were the third most common cause of hand injuries after occupational injury and assault [8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that workplace machines and assault are the most common causes of hand injuries [8]. This calls for enhancement of work place safety measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the majority of these are related to lacerations to the hand [ 6 - 8 ]. Other causes include soft tissue injury (including bruising and amputations), fractures (including dislocations), burns and infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…Hand trauma, in general, often affects the younger population, is greater in the male sex and in the majority of cases is related to occupational, or assault injuries [ 6 , 7 , 10 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Hand trauma, is mainly found in the male sex, affecting the younger population and in the majority of cases is related to work, or assault injuries [1-3]. Data revealed in 2007 by The British Society for Surgery of the Hand [4] showed that 20% of patients attending the emergency room suffered from hand injuries, resulting in more than 1.36 million attendances for hand injuries in the United Kingdom each year.…”
Section: Introductionmentioning
confidence: 99%